Development of an HMI in the LabVIEW Environment for Data Acquisition and Monitoring of Virtual Level Control (Research, Society and Development, 2023)
The purpose of the work is the use of the Level Control scene of the Factory I/O software for level and flow control, as well as the realization of communication with the CodeSys software for the development of an automation and the creation of a Human Machine Interface (HMI), in a LabVIEW environment, which allows decision-making, monitoring and acquisition of level plant data in real time. For this, a virtual environment will be set up in charge of controlling the level of a tank using the PID controller, responsible for keeping the tank level close to the value defined in the setpoint. The controller regulates the liquid flow that will be maintained by the filling valve. Therefore, this work presents the study and literary review of control techniques, identification, automation of industrial processes and HMI development, as well as the methodology, objectives and results of the work.